Peran Profesionalisme Mahasiswa PAI Dalam Membina Akhlak Mulia Siswa SMP IT Al Munadi Medan - Azizah, Ilma Septia; Jannah, Salsabila Nur; Sari, Devi Permata; Siregar, Pani Akhiruddin (Journal of Sustainable Education, 2025)
This research aims to describe the role of professionalism among female students of Islamic Religious Education (PAI) in fostering noble character in students at SMP IT Al Munadi Medan. The early professionalism of PAI students is important to study because they often have dual roles as active students and teachers, as well as making a real contribution to the religious character education of students. This study uses a qualitative approach with a case study method. The research subject is a sixth-semester PAI student who has been teaching since 2021. Data was collected through in-depth interviews, observations of learning and religious activities, and documentation, which were then analyzed using Miles & Huberman's thematic technique. The results show that the professionalism of the subject is manifested in commitment to dual roles, pedagogical skills developed through extensive experience, good time management abilities, and strategies for fostering student character through learning, religious activities, and personal exemplification. Religious activities such as halaqah, MABIT, tahfidz, congregational prayers, and the commemoration of Islamic holidays serve as effective means to internalize moral values such as honesty, discipline, and responsibility. Students' responses to the guidance are very positive, indicating the internalization of religious values. This finding emphasizes that the professionalism of PAI (Islamic Education) students is not only determined by academic status but also by moral, spiritual, and social dedication manifested through real character education practices.